2015
DOI: 10.1002/adfm.201501379
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Carbon Nanotube–Based Flexible Gel Substrates for Engineering Biohybrid Tissue Actuators

Abstract: Muscle-based biohybrid actuators have generated significant interest as the future of biorobotics but so far they move without having much control over their actuation behavior. Integration of microelectrodes into the backbone of these systems may enable guidance during their motion and allow precise control over these actuators with specific activation patterns. Here, we addressed this challenge by developing aligned CNT forest microelectrode arrays and incorporated them into scaffolds for stimulating the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
141
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(141 citation statements)
references
References 43 publications
0
141
0
Order By: Relevance
“…To this end, a combination of myocytes (skeletal muscle cells or cardiomyocytes) and hydrogels that enable communications between these cells is usually adopted. For example, carbon nanotube–composited gelatin methacryloyl hydrogels have been processed into flexible substrates as large as centimeter scales, and cardiomyocytes spontaneously and synchronously beating on the surfaces allow these bioactuators to exhibit rhythmic contraction or extension and swimming behaviors(95, 96). Engineered skeletal muscles, when bound to bioprinted hydrogel frameworks, could also actuate and move the devices in defined patterns (13, 14).…”
Section: Dynamic Modulationmentioning
confidence: 99%
“…To this end, a combination of myocytes (skeletal muscle cells or cardiomyocytes) and hydrogels that enable communications between these cells is usually adopted. For example, carbon nanotube–composited gelatin methacryloyl hydrogels have been processed into flexible substrates as large as centimeter scales, and cardiomyocytes spontaneously and synchronously beating on the surfaces allow these bioactuators to exhibit rhythmic contraction or extension and swimming behaviors(95, 96). Engineered skeletal muscles, when bound to bioprinted hydrogel frameworks, could also actuate and move the devices in defined patterns (13, 14).…”
Section: Dynamic Modulationmentioning
confidence: 99%
“… with permission from Elsevier), carbon NTs (H, adapted from Ref. with permission from John Wiley & Sons), and QDs (I, adapted from Ref. with permission from SAGE Publications).…”
Section: Types Of Nanoparticlesmentioning
confidence: 99%
“…Previous work has shown that engineered biohybrid actuators with anisotropic electrical conductivities can be manipulated to produce cardiac sheets with significantly different excitation thresholds 21 . These data suggest that modulation of directional conductivity cues can impact the functional phenotype of cultured cardiac cells.…”
mentioning
confidence: 99%